A New Socio-Hermeneutics Interpretation of the Landscape Textuality in Otero Pedrayo - Paramá Díaz, Anabel; Gómez Redondo, Susana; Coca, Juan R. (Madrygal. Revista de Estudios Gallegos, 2018)
In this paper we make an analyse of the socio-hermeneutic interpretation that Ramón Otero Pedrayo develops about the Galician Reality, across the landscape. To Otero, the landscape needs to be interpreted, otherwise it is mere externality. In order to understand it, it is necessary to previously approach his particular vision. A vision that allows us to understand the Otero’s thinking and, therefore, his work in a different way. So, in this paper we show the peculiarity of Otero’s textuality of the reality from which he makes a proto-sociological hermeneutics.